2010
DOI: 10.1007/s10681-010-0175-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular mapping of a dwarfing gene in barley (Hordeum vulgare L.) and its correlation with other agronomic traits

Abstract: Ninety-two doubled haploid (DH) lines, generated from a cross between Franklin and TX9425 (a Chinese Landrace), were grown in three environments to identify quantitative trait loci (QTLs) controlling agronomic traits including heading date, plant height and spike characteristics. The DH lines showed a wide range of variations for all the agronomic traits tested. Most of the traits were controlled by one or two major QTLs which explained 9.5-80.9% of the phenotypic variation. Two dwarfing genes were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 30 publications
6
47
1
Order By: Relevance
“…Of the 7 plant height components studied here, the QTL for SL was previously widely reported and detected on all seven chromosomes in barley (Hori et al, 2003;Li et al, 2005;Sameri et al, 2006;Baghizadeh et al, 2007;Wang et al, 2010). In our study, two significant QTL with effect on SL in all 3 years were found.…”
Section: Qtl For Plant Height Componentssupporting
confidence: 74%
See 2 more Smart Citations
“…Of the 7 plant height components studied here, the QTL for SL was previously widely reported and detected on all seven chromosomes in barley (Hori et al, 2003;Li et al, 2005;Sameri et al, 2006;Baghizadeh et al, 2007;Wang et al, 2010). In our study, two significant QTL with effect on SL in all 3 years were found.…”
Section: Qtl For Plant Height Componentssupporting
confidence: 74%
“…In our study, two significant QTL with effect on SL in all 3 years were found. Examining the 2H and 7H linkage maps of Varshney et al (2007) revealed that Qsl2-15 is close to the centromere of the 2HL, and is different from those QTL on chromosomes 2H previously reported (Hori et al, 2003;Li et al, 2005;Sameri et al, 2006;Wang et al, 2010). Qsl7-7 is likely the same as Qel7.1 on chromo-some 7H previously reported (Li et al, 2005).…”
Section: Qtl For Plant Height Componentscontrasting
confidence: 66%
See 1 more Smart Citation
“…The dwarfing gene uzu, and denso were mapped onto the region of chromosome 3HL (Laurie et al 1993: Zhang 2003. Wang et al (2010) identified two QTLs controlling plant height on 3HL. Comparison with the consensus map, the positions of two markers identified here are different from those reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential impact of awn length on yield in barley cultivars, it is important to identify novel QTLs and genes that affect this trait. Previous genetic studies described QTLs for awn length on chromosome 3H (Chen et al 2012; Gyenis et al 2007; Wang et al 2010), possibly co-localizing with either ari - a or semi - brachytic ( uzu ) (HvBRI1); on 6HS (Sun et al 2011); close to the row type locus six - rowed spike 1 ( Vrs1 ) on 2H (Sameri et al 2006), where the awnless locus Lks1 has been mapped; on 7H (Sameri et al 2006), possibly co-localizing with either ari - f or ari - n (Druka et al 2011; Franckowiak and Lundqvist 2012); and on 7HL which is associated with DIMINUTO ( HvDIM ) (Dockter et al 2014). The majority of these studies have investigated the genetic basis of awn length differences in cultivated barley.…”
Section: Introductionmentioning
confidence: 99%